The financial system as an information system that definetely can be improved - Cobarsí-Morales, Josep (Anuario ThinkEPI, 2013)
Key features of the financial system as an information system which links markets´ stakeholders are highlighted and discussed. These features are related to the 2008 subprime crisis, and they are contextualized in sociotechnical changes at the end of the 20th century. Ways to improve the system and prevent future crisis are briefly explored, taking into account information behaviours, which differ from mainstream economics.